Mycelial growth inhibition of fusarium sp. by basil, peppermint and pink palm essential oils - Nascimento, Daniele Maria [UNESP]; Costa Vieira, Gustavo Haralampidou da; Kronka, Adriana Zanin [UNESP] (Univ Estadual Mato Grosso Sul, 2016)
Sudden death syndrome or red root rot, caused by the fungus Fusarium solani f. sp. glycines, has caused serious problems in soybean crop. In this context, this study aimed to evaluate the effect of essential oils of copaiba (Copaifera langsdorfii), neem (Azadirachta indica), basil (Ocimum basilicum), mint (Mentha piperita) and palmarosa (Cymbopogon martinii) on mycelial growth of Fusarium solani f. sp. glycines. Four concentrations of different essential oils [4000, 6000, 8000 and 10000 mu L L-1 of PDA (potato-dextrose-agar) medium] were tested in this study. Mycelium discs of 3.0 mm diameter were inoculated in the center of Petri dishes containing PDA medium with the treatments. Mycelial growth were assessed at seven days after the stablishment of the experiment. Exception the neem and copaiba essential oils, the others essential oils completely inhibited mycelial growth. These results showed the antifungal potential of these essential oils in controlling this disease.
Keywords: alternative control; sudden death syndrome; soybean